Decreased alcohol consumption after pairing alcohol-related cues with an inhibitory response. (4th March 2018) - Kilwein, Tess M.; Bernhardt, Kyle A.; Stryker, Mary L.; Looby, Alison
ABSTRACT: Prior research indicates that repeatedly pairing a stopping response with alcohol-related stimuli using a modified Go/No-Go (GNG) task decreases self-reported drinking by modifying implicit alcohol-related attitudes. The current study replicated and expanded upon this work to better clarify the intervention's lasting effects and pilot ideas for potential mechanisms of action for future research. Forty-four heavy drinking young adult males were randomly assigned to inhibit responses to alcohol (alcohol/No-Go [NG]; n = 23) or water (water/NG; n = 21). At baseline and 2-week post-intervention, participants completed measures of alcohol use, implicit attitudes, alcohol expectancies, response inhibition, and alcohol approach/avoidance. At 2-weeks post-intervention, they participated in an ad-lib drinking session to directly measure drinking behavior. Alcohol/NG participants self-reported lower levels of alcohol use at post-intervention than baseline and took longer to start drinking during the ad lib drinking session in comparison to water/NG participants. In contrast to prior research, the intervention appeared to increase avoidance of alcohol and not significantly alter implicit attitudes. Results indicate that alcohol use measured 2 weeks post-intervention was lower than baseline levels for alcohol/NG participants. The GNG training may offer one path to reducing alcohol use among heavy drinking young adult males for at least 2 weeks.